Antibacterial Test of Bacterial Isolates from Red Rice Syrup - Cut Anisa Sabrina; Suandy Suandy; Linda Chiuman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Red rice syrup, as a fermentation product, contains bioactive components with antimicrobial potential, thereby requiring exploration of the associated microbes and their activities. This study aims to isolate bacteria from fermented red rice syrup, characterize their phenotypic properties, and assess the antibacterial activity of the supernatant against Escherichia coli and Staphylococcus aureus. Isolation was carried out on MRS agar (37 °C, 48 hours), followed by Gram staining, catalase testing, and antibacterial activity testing using the disc diffusion method. Five isolates (SBM1–SBM5) were obtained, all of which were Gram-positive with coccobacillus morphology and catalase-positive. In the antibacterial assay, the supernatant from the five isolates did not produce inhibition zones against either indicator bacterium, whereas the amoxicillin control produced inhibition zones of 13.95 mm (E. coli) and 12.43 mm (S. aureus), and the negative control showed no inhibition. In summary, the isolates from red rice syrup exhibited consistent phenotypic profiles; however, under the test conditions applied, no antibacterial activity was detected against E. coli or S. aureus. These findings provide a foundation for further studies to clarify taxonomic identity and to optimize more sensitive assays for assessing biological activity.